First molecular characterization and taxonomic assessment of Humaria hemisphaerica from Pakistan - Sarwar, Amna Noor; Sarwar, Samina; Naseer, Arooj; Faryad, Ayesha; Sajjad, Nadia; Ali, Hira (Bangladesh Journal of Plant Taxonomy, 2025)
The present study marks the first molecular characterization of Humaria hemisphaerica F.H. Wigg.) Fuckel from the temperate Oghi forest of Khyber Pakhtunkhwa, Pakistan, a region known for its ecological richness and underexplored fungal diversity. A comprehensive description of both the macro- and micro-morphological characteristics is included, supplemented with color photographs of fresh ascocarp in natural habitat and microscopic images with main anatomical features. Phylogenetic analysis of the studied sample was conducted using internal transcribed spacer (ITS) of nrDNA. This analysis supports the taxonomic identification of H. hemisphaerica and confirms its phylogenetic position. Additionally, comparisons are made with closely related taxa that exhibit phenotypic and molecular similarities. This is the first molecular description of this taxon occurring in Pakistan. Bangladesh J. Plant Taxon. 32(2): 129-137, 2025 (December)